Comparative study of haematological parameters of three sturgeon species in recirculating aquaculture system - Sazykin, Ivan; Sazykina, Marina; Gültepe, Nejdet; Khmelectsova, Ludmila E.; Sönmez, Adem Yavuz; Khammami, Margarita I. (Central Marine Fisheries Research Institute, Kochi, 2017)
The aim of this study was to evaluate and compare the haematological parameters of cultured Russian sturgeon (Acipenser gueldenstaedtii), stellate sturgeon (Acipenser stellatus) and Siberian sturgeon (Acipenser baerii) in recirculating aquaculture system. Total erythrocytes, thrombocytes, red blood cell distribution, monocytes, basophils as well as haemoglobin levels of stellate sturgeon differed significantly from that of the other two species (p<0.05). Leukocyte and lymphocyte levels of Siberian sturgeon were significantly higher than in stellate sturgeon and Russian sturgeon (p<0.05). Eosinophil percentages of Siberian sturgeon were significantly lower than stellate sturgeon and Russian sturgeon (p<0.05). Haematocrit levels of stellate sturgeon differed from Siberian sturgeon (p<0.05), but no differences between Siberian and Russian sturgeons were found. Neutrophil, mean cellular haemoglobin and mean cellular volume and mean cellular haemoglobin concentration levels did not differ significantly between the three sturgeon species (p>0.05). The information generated may help in monitoring health status and to adopt better management strategies in culture systems.
Keywords: 14. Life underwater; 6. Clean water; 3. Good health